2010
DOI: 10.1158/1538-7445.am10-4524
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 4524: Targeting Bcl-2 family proteins in adult T-cell leukemia/lymphoma: in vitro and in vivo effects of a novel Bcl-2 family inhibitor, ABT-737

Abstract: Adult T-cell lymphoma/leukemia (ATLL) is a T-cell malignancy caused by the human T-lymphotrophic virus type I (HTLV-I), and its therapeutic outcome still remains extremely poor. Therefore, novel therapeutic strategies are needed to improve treatment outcomes. In this study, we elucidated the therapeutic potential of targeting the anti-apoptotic Bcl-2 family proteins for the treatment of ATLL using ABT-737 (Abbott Laboratories, Abbott Park, IL, USA), a small molecule inhibitor of Bcl-2, Bcl-XL and Bcl-w. We fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Subtype analysis showed that B/My MPAL blast-specific genes included AUTS2 , M EF2A , RB1CC1 , and HBEGF , whereas T/My MPAL blasts overexpressed PTEN , ESYT2 , KMT2C , and PTGG1IP . Heparin-binding epidermal growth factor-like growth factor ( HBEGF ) has been implicated in several cancers including leukemias as an inducer of tumor growth [ 65 67 ], and has previously been targeted in various cancers with small molecule inhibitors [ 67 69 ]. PTEN is typically considered a tumor suppressor gene, with inactivation leading to the development of T-ALL and AML [ 70 , 71 ], thus the significance of PTEN overexpression in T/My blasts needs further exploration.…”
Section: Discussionmentioning
confidence: 99%
“…Subtype analysis showed that B/My MPAL blast-specific genes included AUTS2 , M EF2A , RB1CC1 , and HBEGF , whereas T/My MPAL blasts overexpressed PTEN , ESYT2 , KMT2C , and PTGG1IP . Heparin-binding epidermal growth factor-like growth factor ( HBEGF ) has been implicated in several cancers including leukemias as an inducer of tumor growth [ 65 67 ], and has previously been targeted in various cancers with small molecule inhibitors [ 67 69 ]. PTEN is typically considered a tumor suppressor gene, with inactivation leading to the development of T-ALL and AML [ 70 , 71 ], thus the significance of PTEN overexpression in T/My blasts needs further exploration.…”
Section: Discussionmentioning
confidence: 99%